Analisis Profitabilitas Perusahaan Energi dengan Struktur Modal Sebagai Variabel Moderasi - Bayu, Bayu; Waharini, Faqiatul Mariya (Journal of Economics and Business Research (JUEBIR), 2025)
This research aims to determine the effect of company size, liquidity and managerial ownership on profitability with capital structure as a moderating variable (Study of Energy Sub-sector Companies Listed on the IDX for the period (2021 - 2023). This research uses a quantitative type of research using multiple regression analysis. The sampling technique uses purposive sampling, and a sample of 22 energy sub-sector companies for the 2021-2023 period is obtained. The research results show that the company size variable has a negative but not significant influence on profitability, Liquidity has a positive but not significant influence on profitability, managerial ownership has a positive but not significant influence on profitability. In the results of the Moderate Regression Analysis (MRA) test, the capital structure variable is not able to act as a moderator in the relationship between liquidity and profitability, capital structure is not able to act as a moderator in the relationship between managerial ownership and profitability, and the variable AR(1) has a positive but not significant effect on profitability.